Filsafat Pendidikan di Pesantren Dari Pesan Kyai Menuju Insan Sejati - Akhmad Kuncoro; Siti Masitoh; Mochamad Nursalim (Lembaga Penelitian dan Pendidikan Mandala, 2022)
Islamic boarding schools are one of the hallmarks of this nation's education. Islamic boarding schools have a role related to the philosophy of life. As the oldest education in Indonesia, Islamic boarding schools have at least five pillars, namely Kyai, Santri, Mosque, Al Qur'an and Hadith. There are several aspects that must be strengthened in Islamic boarding schools, namely adab, fardu ain science, fardu kifayah science, administration, networking and so on. Education in Islamic boarding schools is very influential with the surrounding community. The purpose of education in Islamic boarding schools is to educate a person to become an independent person, have good morals, and become someone who is khaira ummah. Regarding the education that is applied in Islamic boarding schools, it can be seen from one of the most frequently encountered principles, namely the principle of non-contradiction. Islamic boarding schools study the science and works of both classical and contemporary scholars in the form of yellow books. And the yellow book is a work that was born from Islamic scholars who sourced from the Koran and Hadith. This principle is based on distinguishing what is right and what is wrong. It is impossible to contradict the Al-Qur'an and hadith which are the main study material in Islamic boarding schools, because both are true sources of Islamic teachings. If someone says the Qur'an and hadith contradict, then it is due to a lack of knowledge in studying and studying them